Intersimple sequence repeat (ISSR) variation in Lactoris fernandeziana (Lactoridaceae), a rare endemic of the Juan Fernández Archipelago, Chile - Crawford, Daniel (2001)
Sixteen populations and 89 individuals of Lactoris fernandeziana were examined for variation in intersimple sequence repeat (ISSR) banding patterns. The species is a rare endemic of Masatierra Island in the Juan Fernandez Archipelago, and is the only member of the endemic family Lactoridaceae. Five populations showed a single genotype whereas the other 11 populations had from two to 16 multilocus genotypes. Over 73% of the ISSR diversity occurred across populations, with only about 27% within populations. Diversity among populations results from the presence of different subsets of loci within each population rather than unique loci within populations; only two populations displayed novel loci, with one and three in each. Levels of differentiation at ISSR loci among populations are not correlated with geographic distance on Masatierra; rather, the pattern of variation is mosaic. The presence of differentiated local populations is concordant with the geitonogamous breeding system of the species and suggests low levels of long distance pollen or seed dispersal. The mosaic pattern of ISSR variation on Masatierra may result, in part, from drift and inbreeding in small populations following fragmentation of a once more continuous distribution of Lactoris with the formation of canyons by erosion. Also, the generation of new ISSR loci by mutation could occur with rare, sporadic gene flow among populations accounting for the mosaic pattern of variation and the paucity of unique alleles within populations. The ISSR results for Lactoris suggest that studies of morphological, ecological and physiological features may elucidate differentiation among populations of L. fernandeziana. Field studies have demonstrated that plants occur both in the dense forest understory and in the full sunlight in forest openings.